Recent advances in the treatment of acute myocardial infarction. - Ferguson, J J (1995)
A number of recent major clinical trials have added substantially to the understanding of what the current "optimal" therapy for acute myocardial infarction may include. This review highlights a number of studies that have been published or presented within the last 2 years. Clearly, there is still room for improvement, but we have made considerable progress in recent years, and the pace of our advances continues to accelerate.